PENGARUH AKSESIBILITAS, WORD OF MOUTH DAN DAYA TARIK WISATA BERPENGARUH TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN KE OBJEK WISATA PANTAI PASIR PUTIH SITUBONDO - Achmad Jaelani; Dassucik Dassucik; Ahmad Hafas Rasyidi (MANAJEMEN, 2025)
This study aims to analyze the influence of accessibility, word of mouth, and tourist attraction on the decision to visit Pasir Putih Beach in Situbondo. The research uses a quantitative approach. The sampling technique applied is non-probability sampling with a purposive sampling method, involving 100 respondents. Data were collected using a questionnaire measured with a Likert scale and analyzed using SPSS version 23.